1998
DOI: 10.1038/sj.bmt.1701053
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic abnormalities after autologous stem cell transplantation in lymphoma patients

Abstract: Summary:Haematopoietic reconstitution after autologous stem cell transplantation (ASCT) was evaluated at different times in 26 lymphoma patients. All of the patients showed a significant decrease in the number of both committed (CFU-C) and more primitive progenitor cells (LTC-IC). The expansion of bone marrow progenitor cells in a 'stroma-free' long-term liquid culture system supplemented with SCF, IL-3, IL-6 and GM-CSF from 19 transplanted patients was significantly reduced compared to normal controls. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
(13 reference statements)
1
18
1
Order By: Relevance
“…25 To our knowledge, only one case with a single trisomy X has been described as a secondary MDS (refractory anemia subtype), which developed 4 months after ASCT in a patient with Hodgkin's lymphoma. 30,31 Unlike our cases, the patient died 2 months after the onset of MDS. Nevertheless, this case may be similar to ours with trisomy X.…”
Section: Discussioncontrasting
confidence: 40%
“…25 To our knowledge, only one case with a single trisomy X has been described as a secondary MDS (refractory anemia subtype), which developed 4 months after ASCT in a patient with Hodgkin's lymphoma. 30,31 Unlike our cases, the patient died 2 months after the onset of MDS. Nevertheless, this case may be similar to ours with trisomy X.…”
Section: Discussioncontrasting
confidence: 40%
“…These data are in agreement with previous reports, showing a damage of the marrow microenvironment after bone marrow transplantation or the administration of cytostatic drugs. [25][26][27] Based on these data it can be said that in remission phase of NHL patients perturbations and physiological stress such as those that may occur in the BM after chemotherapy do not prevent the growth of endothelial cells in contrast to what happened to the fibroblast component of the BM. The persistence of ECs may contribute to the bone marrow hematopoietic reconstitution by producing potent stimulating factors such as b-FGF, which, under acidosis conditions, has been shown to stimulate EC proliferation and protection from apoptosis, 28 or VEGF that can be produced in larger amounts by repopulating progenitors, which can ultimately stimulate (by a paracrine loop) the proliferation of both immature (angioblasts) and differentiated endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of dyserythropoietic and dysthrombopoietic atypias has been previously restricted to the early post-transplant period (first 12 weeks) after transplantation. [19][20][21] Transient dyserythropoiesis has been reported to be present in all cases 60 days following transplantation. 20 We have found that dyserythropoietic changes persist in some cases for a long time after autografting, although usually only a minority of erythroblasts are affected.…”
Section: Cytopeniasmentioning
confidence: 99%
“…Information about the influence of transplantation on bone marrow cellularity is scanty. [21][22][23][24] We have observed that the transplant process induces hematopoietic damage, increasing the number of cases with decreased cellularity and thrombopoiesis 6 months after the procedure. However, this damage is transitory since these parameters return to normal in most patients 1 year after transplantation.…”
Section: Tablementioning
confidence: 99%